The relationship between structural empowerment, attitudes and competencies practice in Malaysia Welfare Department - Md Noor, Amna; Ahmad Shuhaimi, Noorhaizah; Wan Jaafar, Wan Munira (Secholian Publication, 2024)
This study meticulously examines the intricate relationship between structural empowerment, attitudes (specifically job satisfaction, commitment, and trust), and behaviors, on their impact on practical competencies in the realm of social work. The participants, drawn from the Department of Social Welfare's Social Scheme, underwent analysis using the SPSS survey and revealed a statistically significant and positive correlation between structural empowerment, attitudes and behaviors with practical competencies as indicated in the motion. Crucially, the study also identifies resources and support as key variables which exert a pivotal influence on competencies at workplace. The findings underscore the critical imperative of enhancing structural empowerment, attitudes, and behaviors to elevate competencies within the social work domain. The study also strongly advocates for organizational prioritization of structural empowerment improvements and the provision of substantial support, fortifying social workers' competencies and thereby enhancing the overall effectiveness of social services.